(untitled) (REMUNOM, 2024)
This study addresses urban erosion processes in Gurupi, Tocantins, focusing on their causes, impacts, and potential solutions. The research was conducted in areas of the city facing challenges due to the lack of proper planning for stormwater management. The methodology included geological and pedological analysis, as well as field inspections to identify signs of erosion, such as ravines and gullies. The results indicated the presence of erosional features in specific locations, especially in lower-lying areas with deficient drainage infrastructure. The study also highlighted the importance of practical interventions, such as improving drainage systems and sustainable urban planning, to mitigate erosional impacts and increase the city’s resilience to climate change and population growth. The implementation of adequate measures can help prevent the progression of erosional processes, ensuring environmental preservation and urban quality of life.